THE EFFECT OF DENTAL HEALTH EDUCATION USING THE DEMONSTRATION METHOD ON THE BEHAVIOR OF DENTAL BRUSHING IN CLASS V SCHOOL AGE CHILDREN AT SDN 1 PAGAR AIR DISTRICT WANTS TO JAYA DISTRICT BIG ACEH - Reca; Dea Pradia Asri (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
Dental and oral health counseling to elementary school students is one of the efforts to improve the degree of dental health in children in promotive and preventive aspects. The selection of demonstration methods in dental and oral health education supports increasing children's understanding, by practicing directly how to brush their teeth correctly. From the results of interviews with 10 students, it is known that 7 students do not know how to brush their teeth properly and correctly. This study aims to determine the effect of dental health education using the demonstration method on tooth brushing behavior in fifth grade school-aged children at SDN 1 Pagar Air, Want Jaya District, Aceh Besar District. The type of research used in this study is a Quasi Experiment using a pretest and posttest design which was carried out on January 21-22 2022 at SDN 1 Pagar Air, Aceh Besar District. The sampling technique was Total Sampling, which consisted of 60 students. Analysis of the data in this study is quantitative data using parametric statistical test Paired Sample T-test. The results showed that there was an effect of dental health education using the demonstration method on tooth brushing behavior in fifth grade school-aged children at SDN 1 Pagar Air with a significant value of P =. p=0.000. It can be concluded that there is an effect of dental health education using the demonstration method on the behavior of brushing teeth in fifth grade school-aged children at SDN 1 Pagar Air. It is suggested to the students of SDN 1 Pagar Air, Sub-District of Want Jaya to apply good and correct brushing techniques.